Key diagnostic features of fever of unknown origin: Medical history and physical findings. (23rd May 2017) - Takeda, Rinne; Mizooka, Masafumi; Kobayashi, Tomoki; Kishikawa, Nobusuke; Yokobayashi, Kenichi; Kanno, Keishi; Tazuma, Susumu
Abstract: Background: Fever of unknown origin (FUO) has many possible causes, so detailed history taking and physical examination are required. We identified key diagnostic features of medical history and physical findings for an efficient diagnosis of FUO. Methods: A total of 42 consecutive patients (mean age: 50.6±20.3 years) with classic FUO were retrospectively recruited from January 2010 to March 2012. Key diagnostic features were identified from among diagnostic criteria for underlying diseases, indicators for diagnostic tests, and more useful factors for differential diagnosis. Results: The mean number of abnormal findings per patient was 5.8 from taking the history and 2.0 from performing physical examination. In addition, the mean number of key diagnostic features identified was 0.7 (14.0%) from history taking and 0.6 (35.0%) from physical examination. The most relevant key diagnostic feature was arthritis, followed by cervical lymphadenopathy, dyspnea (with hypoxia), and ocular symptoms. Conclusion: The usefulness of certain features of medical history and physical findings for diagnosing FUO was determined. Focusing on arthritis, cervical lymphadenopathy, dyspnea with hypoxia, and ocular symptoms might improve diagnostic efficiency in patients with FUO.